Impact of swiping direction on the interaction performance of elderly-oriented smart home interface: EEG and eye-tracking evidence - Zhou, Chengmin; Shi, Ziyan; Huang, Ting; Zhao, Hanxiao; Kaner, Jake (Frontiers in Psychology, 2023)
Smart home technology is increasingly popular, yet not all seniors are receptive and comfortable with it. This situation recognizes that the usability of the smart home interfaces is particularly important. Most studies on interface swiping direction demonstrate the advantages of horizontal over vertical swiping, but the findings lack age-based as well as gender-specific judgments. In this paper, we use cognitive neural techniques of EEG and eye-tracking, combined with a subjective preference questionnaire, to analyse the preference of older persons for the swiping direction of smart home interfaces in a multimodal manner. The EEG data showed that swiping direction had a significant effect on potential values (p=0.001). Also, the mean power in the delta and the theta band was enhanced during vertical swiping. Gender had no significant effect on potential values (p=0.085), but the cognitive task was more EEG stimulating for females. The eye-tracking metrics data showed a significant effect of swiping direction on fixation duration (p=0.047) and a non-significant effect on pupil diameter (p=0.576). These results were consistent with the results of the subjective preference questionnaire, both demonstrating a preference for vertical swiping among participants. This paper uses three research tools simultaneously, combining objective perceptions as well as subjective preferences, to make the findings more comprehensive and reliable. Gender differences were also taken into account and differentiated in the data processing. The findings of this paper are different from most previous studies and better reflect the preference of elderly people for swiping directions, which can provide a reference for the future elderly-friendly smart home interface design.